'Thinking about pain in a different way': Patient perspectives of a neuroscience-informed physiotherapy programme for rotator cuff-related shoulder pain. (February 2023) - Acker, Rosemary; Swain, Nicola; Perry, Meredith; Wassinger, Craig; Sole, Gisela
Abstract: Background: Rotator cuff-related shoulder pain (RCRSP) is a common musculoskeletal problem. The multi-factorial contributors to persistent pain are often overlooked during treatment. Pain neuroscience education (PNE) contributes to a holistic approach for patients with persistent pain but has not yet been researched for patients with RCRSP. Objective: To explore the perspectives and experiences of participants with RCRSP who had completed a programme of PNE-informed pragmatic physiotherapy. Design: A qualitative study using semi-structured interviews. Methods: We included a sub-group of five males and five females, aged 46–75 years, with persistent RCRSP of at least three months. They had undertaken a three-month pragmatic physiotherapy integrated with PNE. Individual semi-structured interviews were recorded, transcribed verbatim, and analysed using the General Inductive Approach. Results: Four themes emanated from the interviews. The first two themes were named 'Patient Beliefs' and overall 'Rapport and Relationship'. Another theme, 'Perspective and Understanding of the Resources', indicated diverse uptake of the resource information. The participants reported developing self-management skills, active coping strategies and a reduction in fear of pain described by the theme: 'Empowerment: My Shoulder into the Future'. Conclusions: Participants experienced a change in their beliefs, which were enhanced by an individualised delivery and a strong therapeutic relationship through the course of the physiotherapy care. The participants appeared to value when the physiotherapist listened to and understood their beliefs. This required a shift in the patient-therapist relationship from the physiotherapist being the 'expert' to facilitating the patient's ability to take control of their shoulder health. Highlights: 10 people with shoulder pain described their experience of neuroscience pain education. Those with low buy-in for PNE still had improved self-efficacy. They all described improved self-management of their shoulder pain. All participants described a strong therapeutic alliance. PNE can be integrated with 'usual' physiotherapy for shoulder pain.